Ancient Egypt : An Illustrated History - Oakes, Lorna; Gahlin, Lucia (Leicester Lorenz Books, 2018)
A detailed history with fascinating insights and a gorgeous visual reference, this book tours the sacred Egyptian sites, from the impressive mortuary temples of the pharaohs to those dedicated to the many gods and goddesses. It includes an in-depth examination of the crucial role that religious belief and mythology played during this intriguing period of ancient history.
Part one: Sacred sites of Ancient Egypt. Burial places -- Relgious centres -- Part two: Gods, myths, and religion of Ancient Egypt. State religion -- Religion in life and death.
Keywords: To 332 B.C; Architecture, Ancient -- Egypt; Historic sites -- Egypt; Antiquities; Architecture, Ancient; Civilization; Historic sites; Mythology; Religion; Egypt -- History -- To 332 B.C; Egypt -- Civilization -- To 332 B.C; Egypt -- Antiquities; Egypt -- Religion; Egypt -- Mythology; Egypt; History